2021
DOI: 10.24329/aspikom.v6i1.750
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Instagram Stories at the Age of COVID-19 Pandemic

Abstract: One of Instagram's features, Instagram stories (IS), which allows users to access videos and photos for 24 hours, is one of the prevalent features used by Instagram users. This qualitative research aims to investigate the use of IS during the COVID-19 pandemic by referring to The Technology Acceptance Model (TAM) as a research framework. The framework observes ten external factors that influence the perception of ease of use and IS's usefulness, affecting the user's attitude to IS, leading to IS's actual use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Google For those whose content is focused on education, they get their ideas through articles found on the Google search page The closer and closer to the audience, the more interested the audience is, for example, about partners, heartbreak, touching messages, or personal experience stories can be interesting content for MSMEs so that they have an immediate sense of closeness to the content. According to Robin in Savitri and Irwansyah (2021), showing emotion is the most popular type of storytelling in the digital world, one of which is telling someone's experience. In this context, SMEs can share their stories about their experiences in business.…”
Section: Content Qualitymentioning
confidence: 99%
“…Google For those whose content is focused on education, they get their ideas through articles found on the Google search page The closer and closer to the audience, the more interested the audience is, for example, about partners, heartbreak, touching messages, or personal experience stories can be interesting content for MSMEs so that they have an immediate sense of closeness to the content. According to Robin in Savitri and Irwansyah (2021), showing emotion is the most popular type of storytelling in the digital world, one of which is telling someone's experience. In this context, SMEs can share their stories about their experiences in business.…”
Section: Content Qualitymentioning
confidence: 99%
“…According to Smith and Anderson (2018), Instagram is the most used social media site by young adults. Instagram is one of the most prominent social media sites soon after Facebook and Google+ (Kocak, Nasir, & Turker, 2020;Savitri & Irwansyah., 2021). In addition to popularity, the researcher chose Instagram for the following reasons:…”
Section: Instagram Rationalementioning
confidence: 99%
“…foreign language learning as they develop conversation and give an insight into how to use a language in an informal manner which adds sociolinguistic features to the language (Gomes Junior, 2020; S. Lim & Yazdanifard, 2014;Savitri & Irwansyah., 2021).…”
Section: Instagram Rationalementioning
confidence: 99%
“…Students were given digital literacy in using social media regarding finding information about COVID-19 by verifying information before disseminating information on their social media accounts (Junaedi & Sukmono, 2020). Finally, a research (Savitri & Irwansyah, 2021) has successfully found patterns and forms of uploading COVID-19 news on Instagram stories and became a relevant reference for this research. From those explanations, this research is expected to complement previous research that focuses on media users, especially Instagram, and examine the public's attitudes as vaccine recipients.…”
Section: Introductionmentioning
confidence: 99%